Target actionability review: a systematic evaluation of replication stress as a therapeutic target for paediatric solid malignancies - Keller, Kaylee M.; Krausert, Sonja; Gopisetty, Apurva; Luedtke, Dan; Koster, Jan; Schubert, Nil A.; Rodríguez, Ana; van Hooff, Sander R.; Stichel, Damian; Dolman, M. Emmy M.; Vassal, Gilles; Pfister, Stefan; et al. (European journal of cancer, 2022)
Background - Owing to the high numbers of paediatric cancer-related deaths, advances in therapeutic options for childhood cancer is a heavily studied field, especially over the past decade. Classical chemotherapy offers some therapeutic benefit but has proven long-term complications in survivors, and there is an urgent need to identify novel target-driven therapies. Replication stress is a major cause of genomic instability in cancer, triggering the stalling of the replication fork. Failure of molecular response by DNA damage checkpoints, DNA repair mechanisms and restarting the replication forks can exacerbate replication stress and initiate cell death pathways, thus presenting as a novel therapeutic target. To bridge the gap between preclinical evidence and clinical utility thereof, we apply the literature-driven systematic target actionability review methodology to published proof-of-concept (PoC) data related to the process of replication stress. - Methods - A meticulous PubMed literature search was performed to gather replication stress-related articles (published between 2014 and 2021) across 16 different paediatric solid tumour types. Articles that fulfilled inclusion criteria were uploaded into the R2 informatics platform [r2.amc.nl] and assessed by critical appraisal. Key evidence based on nine pre-established PoC modules was summarised, and scores based on the quality and outcome of each study were assigned by two separate reviewers. Articles with discordant modules/scores were re-scored by a third independent reviewer, and a final consensus score was agreed upon by adjudication between all three reviewers. To visualise the final scores, an interactive heatmap summarising the evidence and scores associated with each PoC module across all, including paediatric tumour types, were generated. - Results and conclusions - : 145 publications related to targeting replication stress in paediatric tumours were systematically reviewed with an emphasis on DNA repair pathways and cell cycle checkpoint control. Although various targets in these pathways have been studied in these diseases to different extents, the results of this extensive literature search show that ATR, CHK1, PARP or WEE1 are the most promising targets using either single agents or in combination with chemotherapy or radiotherapy in neuroblastoma, osteosarcoma, high-grade glioma or medulloblastoma. Targeting these pathways in other paediatric malignancies may work as well, but here, the evidence was more limited. The evidence for other targets (such as ATM and DNA-PK) was also limited but showed promising results in some malignancies and requires more studies in other tumour types. Overall, we have created an extensive overview of targeting replication stress across 16 paediatric tumour types, which can be explored using the interactive heatmap on the R2 target actionability review platform [https://hgserver1.amc.nl/cgi-bin/r2/main.cgi?option=imi2_targetmap_v1].